2021
DOI: 10.1038/s41598-020-80193-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of kinase IKKβ suppresses cellular abnormalities induced by the human papillomavirus oncoprotein HPV 18E6

Abstract: Human papillomavirus (HPV) is the leading cause of cervical cancer and has been implicated in several other cancer types including vaginal, vulvar, penile, and oropharyngeal cancers. Despite the recent availability of a vaccine, there are still over 310,000 deaths each year worldwide. Current treatments for HPV-mediated cancers show limited efficacy, and would benefit from improved understanding of disease mechanisms. Recently, we developed a Drosophila ‘HPV 18 E6’ model that displayed loss of cellular morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Our recent study has shown that the reduced expression of IKKβ leads to suppression of the cellular abnormalities induced by cooperative action of E6 and hUBE3A and that the interaction of IKKβ and E6 is conserved in human cells ( Padash Barmchi et al , 2021 ). In order to identify the genes that play a role in IKKβ-mediated suppression of E6-induced defects, we compared the transcriptome profile of the cells expressing E6 + hUBE3A and cells expressing E6 + hUBE3A with a reduced level of IKKβ.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent study has shown that the reduced expression of IKKβ leads to suppression of the cellular abnormalities induced by cooperative action of E6 and hUBE3A and that the interaction of IKKβ and E6 is conserved in human cells ( Padash Barmchi et al , 2021 ). In order to identify the genes that play a role in IKKβ-mediated suppression of E6-induced defects, we compared the transcriptome profile of the cells expressing E6 + hUBE3A and cells expressing E6 + hUBE3A with a reduced level of IKKβ.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this view we found a significant reduction in the level of alpha-Catenin in tissues expressing E6 + hUBE3A + one functional genomic copy of IKKβ. This strong downregulation of alpha-Catenin is expected as it likely leads to inactivation of Yorkie and normalization of tissue growth and size, a phenotype that was observed when IKKβ was reduced in eye tissues expressing E6 + hUBE3A ( Padash Barmchi et al , 2021 ). alpha-Catenin has also been shown to act as tumor suppressor in breast cancer cells by interacting with IκBα, which in turn results in stabilization of IκBα and inhibition of the NF-κB signaling ( Piao et al , 2014 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly fruit flies have played important role in understanding the mechanisms underlying the interactions between pathogens including viruses with their host, uncovering the molecular mechanism of tissue regeneration, and identifying new therapeutics derived from plants and other organisms [ 45 47 ]. We have previously established a Drosophila model of HPV18-induced cell deregulation and successfully used it to identify important players in inducing the cellular abnormalities caused by HPV18 oncogenes [ 48 , 49 ]. Therefore, a Drosophila model of HPV16-induced cancer will be a powerful complement to existing in vitro and transgenic mice models in the study of cancerous pathways driven by HPV16 oncogenes.…”
Section: Introductionmentioning
confidence: 99%